Developing Songs for Children to Upgrade the Arabic Vocabulary Comprehension/تطوير الأغاني للأطفال لترقية استيعاب المفردات العربية - Aldena, Soraya (Jurnal Al-Maqoyis, 2021)
Singing is one of the activities that children prefer almost all children listen to the songs they listen to, especially if the singing is followed by physical movements Almost all children listen to the songs they listen to, especially if the singing is followed by physical movements. Vocabulary is an essential component of language and it plays an important role in the linguistic process, both verbally and in writing there is no doubt that it makes singing a teaching method for teaching Arabic vocabulary, especially in the elementary stage. the method used in this research, it is the method of research, development and experimental, with qualitative and quantitative input, The researcher used the developmental research steps of Sogiyono, but the researcher only performed five steps It is an arbitration of experts and makes this arbitration to know the validity of the developed songs for children in teaching vocabulary to the pupils of the elementary school Normal Islam Rasyidiyah Khalidiyah Amuntai.